1975
DOI: 10.1128/jb.123.3.962-971.1975
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhibition of protein synthesis on lipid metabolism in Lactobacillus plantarum

Abstract: In Lactobacillus plantarum 17-5, lipid synthesis appears to be correlated with protein synthesis. Inhibition of protein synthesis by chloramphenicol (50,ug/ml)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…The crude fat content also showed a marginal increase in LPFT and BLFT (4% and 7.3% respectively), which can be attributed to the production of fatty acids by the bacterial strains. The increase in the crude fat content could be correlated with the increase in the protein content as reported by Arbogast and Henderson (1975), in that the polar lipid synthesis is associated with the protein synthesis because the enzymes required for the lipid synthesis are to be replaced by de novo protein synthesis. As such, fish wastes have a very low fibre content and it requires no further discussion, for the low crude fibre content in both LPFT and BLFT.…”
Section: Resultssupporting
confidence: 52%
“…The crude fat content also showed a marginal increase in LPFT and BLFT (4% and 7.3% respectively), which can be attributed to the production of fatty acids by the bacterial strains. The increase in the crude fat content could be correlated with the increase in the protein content as reported by Arbogast and Henderson (1975), in that the polar lipid synthesis is associated with the protein synthesis because the enzymes required for the lipid synthesis are to be replaced by de novo protein synthesis. As such, fish wastes have a very low fibre content and it requires no further discussion, for the low crude fibre content in both LPFT and BLFT.…”
Section: Resultssupporting
confidence: 52%
“…An analysis of residual divisions after the initiation of antibiotic treatment indicated that cerulenin affected an event about 43 min before the cessation of division and approximately 10 min before the termination of chromosomal replication as determined by treatment of similar cultures with mitomycin C. Transient increases in lipid synthesis have been reported in the late stages of the cell division cycle in bacteria (6,11). Also, observations in many other bacterial species (1,9,10,13,16,20) are consistent with a primary lipid involvement in the cell division process. The present study suggests that cerulenin, which blocks de novo lipid and LTA synthesis, can block a crucial cell division event.…”
Section: Resultsmentioning
confidence: 93%
“…(2005) reported that in LAB, the citric acid once inside the cell is split into acetate and oxaloacetate by the citrate lyase enzyme. The acetate formed can be expelled or part of it can be used in biosynthetic reactions, such as fatty acid synthesis (Arbogast and Henderson 1975; Goldberg and Eschar 1977). These facts could explain the decrease in acetic acid concentrations observed in CDM without Cit.…”
Section: Discussionmentioning
confidence: 99%